Analysis of a Parallel Informal Exchange Rate System in Indo-Bhutanese Border Towns. Issue 4 (8th August 2021) - Sharma, Ankur
ABSTRACT: The Bhutanese Ngultrum and the Indian Rupee follow a fixed exchange rate system but within the border towns between India and Bhutan, an informal exchange rate system exists, which in contrast, is primarily based on market value system. The researcher aimed to study the underlying dynamics associated with an informal exchange rate system co-existing with the official market rate within the borderland regions of India and Bhutan. This research was focussed primarily upon intensive research methodology through interactive interviews, qualitative analysis and, primarily, in-site participant observation research techniques.